Perancangan User Interface Menggunakan Metode User Centered Design Pada Aplikasi PUSPA RSUD. Moh Anwar Sumenep Untuk Pengguna Lansia - Sulthan Muhammad Fauzan Laksono; Erna Selviyanti; Maya Weka Santi; Mudafiq Riyan Pratama (Jurnal Rekam Medik & Manajemen Informasi Kesehatan, 2024)
Hospitals need to provide services that prioritize safety, health, comfort and convenience. Hospital staff reported that many elderly patients do not bring complete personal data and are often confused by the information in the application, especially regarding SPM, BPJS, and payment rates, even though the information is available. A usability test was conducted on the PUSPA application at Moh. Anwar Hospital involving 7 respondents using the System Usability Scale (SUS) method. The test results showed a usability score of 48.21, which is in the poor category. This study aims to redesign the user interface of the PUSPA application with a user-centered design approach. The method used is a combination of qualitative and quantitative approaches through interviews and questionnaires to collect data. The redesigned interface was evaluated using the SUS and UEQ tests. The SUS score increased to 70.71, indicating a good category. The UEQ test results for the new interface showed a "good" rating for the clarity and efficiency variables, and "above average" for attractiveness, reliability, stimulation, and novelty, so that application design updates need to be implemented immediately.